Adapting to Change: The Effects of Case Study Approaches on Problem-Solving Skills - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath; Ahmar, Ansari Saleh (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study is to determine whether the case study methodology has a substantial effect on students' problem-solving skills when compared to traditional learning approaches. The research sample consisted of 56 students divided into two groups: experimental (taught using the case study approach) and control (taught using the traditional method). The quantitative quasi-experiment approach was applied in this study. The experimental class had an average value of 70.7143, whereas the control class had an average value of 62.1429. The independent t-test yielded a significance value of 0.055, suggesting a degree of significance lower than the standard criterion of 0.05. The key conclusion of this study is that employing case studies improves soft skills during the learning process. However, the development of pupils' hard skills is still seen as minor. This study contributes to a better understanding of the influence of the case study technique on problem-solving learning. These findings may be used to provide practical recommendations to increase the efficacy of learning methodologies in acquiring both types of abilities. More study is needed to investigate the elements that impact the observed outcomes and increase the statistical significance in the development of students' skills.